The Choise of Feedback Gains in the Computer Model-Based Control Systems of the Direct-Drive Manipulator - Kowalska, Z. (Engineering Transactions, 1994)
The paper presents the results of simulations which were carried out in order to work out the methods of selection of control parameters for two control systems: a) the relatively simple control system with PD compensators of position errors and feedforward compensation of gravitational forces, b) the inverse dynamic control system. For both control systems two procedures of choice of the control parameters are presented: a) the procedure based on the analysis of simplified models of plants and controllers, b) the procedure consisting in numerical optimization of an integral performance index.